Predictors of the level of Knowledge, Attitude and Practices of HIV & AIDS - Karki, Tej Bahadur (Journal of Advanced Academic Research, 2017)
The study was conducted with the aim to explore the predictors of the level of knowledge, attitude, practices of HIV and AIDS. The study was conducted among the 404 respondents of 15-49 years in Kathmandu valley, Nepal. Quantitative technique was adopted during the data collection. Respondents were selected by using the simple random sampling. Linear regression model was used to find out the impact of demographic variables and social factors on level of knowledge, attitude and practices of HIV and AIDS. The result shows that the demographic variables only explain 10.80% of the variation in the knowledge, 39.40% of the variation in the attitude towards the HIV and AIDS and 33.10% of the variation in the practices of HIV and AIDS. Similarly, individual factors (IF), political factors (PF), educational factors (EF), economic factors (EcoF) and socio-cultural factors (SCF) only explains 17.7% of the variation in the knowledge, 12.40% of the variation in the attitude towards HIV and AIDS and  5.01% of the variation in the practices of HIV and AIDS. Individual should be sincere in his/her behavior and practices to reduce the risk of HIV transmission. Besides that, Government should take the responsibilities to address the other factors associated with risk of HIV and AIDS.Journal of Advanced Academic Research Vol. 3, No. 2, 2016, Page: 115-127